Research progress of neuron-specific enolase in cognitive disorder: a mini review - Liu, Fang; Li, Haiyan; Hong, Xiaqing; Liu, Ying; Yu, Ze (Frontiers in Human Neuroscience, 2024)
Numerous studies have demonstrated that neuron-specific enolase (NSE) serves as a distinctive indicator of neuronal injury, with its concentration in blood reflecting the extent and magnitude of nervous system damage, and the expression of serum NSE is correlated with cognitive dysfunction.The assessment of NSE holds significant importance in diagnosing cognitive dysfunction, assessing disease severity, predicting prognosis, and guiding treatment. In this review, the research progress of NSE in cognitive dysfunction was reviewed, and the value of serum NSE level in predicting disease severity and prognosis of patients with cognitive dysfunction was discussed.